The classroom challenges and strategies: The reflection of perceived meaning of inclusive education of teachers in inclusive schools - Savira, Siti Ina; Wagino, Wagino; Normalia, Normalia (Lembaran Ilmu Kependidikan, 2023)
This article aims to describe how teachers identify the classroom challenges and strategies as a reflection of their held meanings of inclusive education. The research data was obtained from 20 teachers who filled out short fills from questionnaires distributed online. Data is analyzed using thematic analysis where data is reduced and categorized into themes and subthemes based on similarity. The results show that teachers tend to use stricter view on inclusive education as education intended for children with special needs, while the challenges faced by teachers in the classroom include challenges related to social aspects, such as how to communicate and interact with students with disabilities, understand the needs and character of variations in existing disabilities, and pedagogical challenges, such as providing instruction,  material, as well as classroom management. Strategies used by teachers include communication strategies and psychological approaches to deal with the social aspects of the challenges faced, and pedagogical strategies to overcome challenges in classroom teaching. The results of this study show the importance of social and pedagogic competence for teachers in adapting to the complexity in the classroom.